THE SPIRITUAL SEARCH OF ART OVER ISLAMIC ARCHITECTURE WITH NON-FIGURATIVE REPRESENTATIONS - Ahmed, Ar Sayed (Journal of Islamic Architecture, 2014)
Art behind Islamic architecture actually based on geometric patterns, developed through a continuous practiceover the centuries after centuries by the influences of various earlier cultures such as Greek, Roman,Byzantine, Central Asian and Persian. Basic shapes like squares and rectangles play significant role in Islamicarchitecture.The reason is, it might recall the principles that govern the order of the world- ‘Purity’, couldonly be resembled by pure forms. The façades built by rectangular bricks tend to shape the built form inregular modules. This brickwork casts shadows in strong desert sunlight and creates a three-dimensional effectas light is welcoming message from the Devine source, as it is regarded in all religions. In addition, variouspointed starry patterns are common practice and get extremely complex when the outer points are joinedtogether and intersections are connected in a systematic way. Another mode is based on organism of floralforms which recalls the feminine nature of life giving. Again, nobody will argue about the contribution ofcalligraphy is the most patronized art for decoration. Why have Islamic world choose this universal phenomena?As Allah’s creation is pre-decided, the credit of all creativity belongs to the almighty. Also to his messenger,the holy prophet; who taught us to think in this way. The world is only a shadow of real world; here man is on abewildered search. May be their firm belief; what man can perceive, can only discover the geometric forms toconstitute designs which were already existed before in the ‘real world’. Discovered geometric forms,therefore, tries to exemplify that perfect reality because creation of Allah has been obscured by the sins ofmankind- Art of the complete surrender.